Evaluation and optimal selection of Carboniferous Kalashayi Formation source rocks in southwestern Tarim Basin - ZHANG Fushun, ZHENG Qiming, HU Hanwen, YAO Wei, ZHANG Tan, MA Hongqiang (Youqicang pingjia yu kaifa)
The study explores the abundant oil and gas reserves in the Carboniferous of the southwestern Tarim Basin, with a specific focus on the source rocks of the Carboniferous Kalashayi Formation. By conducting kerogen identification, total organic carbon（TOC） testing, and thermal simulation, the research revealed that these mudstone source rocks primarily consist of Type Ⅲ kerogen. Their TOC ranged from 0.2% to 2.8%, averaging 1.0%. The thermal maturity of the rocks, indicated by a vitrinite reflectance（Ro） greater than 0.7%, varied across different areas. The hydrocarbon generation history of these source rocks was also examined. In the Magaiti slope, the rocks underwent two phases of hydrocarbon generation: one during the Late Hercynian period and another during the Himeyama period. In contrast, in the Bachu bulge, there was only one hydrocarbon generation phase, occurring during the Late Hercynian period. The source rocks in the Magaiti slope are considered mature and are still generating hydrocarbons, influenced by factors such as source rock thickness, TOC, maturity, and the history of hydrocarbon generation and excretion. Furthermore, the source rocks in the western piedmont zone were identified as having the best quality and the highest hydrocarbon generation intensity.